Effect of Different Ratio Omega-3 and Omega-6 in Total Mix Ration on Productive Performance, Blood Metabolites and Estrous Characteristic of Ewes - Yusti Pujiawati; Lilis Khotijah; Asep Sudarman; Indah Wijayanti (Buletin Peternakan, 2018)
This study was conducted to compare the effect of different ratio of omega-3:omega-6 in total mix ration to blood metabolites and reproductive performance of ewes. A total of 25 young ewes were randomly assigned to five experimental groups and five replications : R0 (without omega-3:omega-6), R1 (omega-3:omega-6 1:8), R2 (omega-3:omega-6 1:6), R3 (omega-3:omega-6 1:3), R4 (omega-3:omega-6 1:2). The parameters measured were feed intake, productive performance, blood glucose and cholesterol pre-mating period. Parameters of characteristic estrous measured were onset of estrous, length of estrous and estrous response. The result showed that ratio of omega-3 and omega-6 1:2 have a greatest daily weight gain and feed efficiency. Ratio of omega-3 and omega-6 1:2 have blood glucose lowest, but highest blood cholesterol. Addition of omega-3 cause to delays onset of estrous. The conclusion is greatest length of estrous, estrous response and pregnacy rate on ratio of omega-3 and omega-6 1:2 in ration.